DEIXIS ON TRIBUNNEWS.COM “THE STORY OF ADE JIGO WAS ROLLED UP BY THE TSUNAMI 2018” - Jasmine Adinda Putri; Yana Yana (IKIP Siliwangi, 2020)
This research aims to identify words contain the deixis from Tribunnews.com and then describes the factors of the deixis that also give more understanding to the reader about types of deixis which are used in tribunnews.com. The researchers used a descriptive qualitative method to analyze the words contained in Tribunnew.com. Data collection used by the researchers is documentation, there are: collecting the data, reading and observing, finding the data, putting sign and making a checklist on it, taking and presenting them in the data display, and finding con clusions. Moreover, the researchers found the deixis in the news that the word of I (24.51%), we (1.96%), he (8.82%), calling name (6.86%), kindship lexemes (32.35%). The word of place or location like a beach, Krakatau mountain, etc is spatial deixis is a place (9.80%) and adverb of place (8.82%). And the last the use of time such as then, now, soon, day, today, etc is the temporal deixis there are deictic Modifier (2.94%) and non-deictic (3.92%). From this research, the researchers conclude that online article creates a narrative in the news that discusses natural disasters, uses a lot of deixes to the person, place, and time.Keywords: Deixis, Tribunnews, Pragmatics